Cores nas telas animadas - Victória de Freitas Arruda (2023)
This research aimed to contribute to understanding the role of colors in the construction of animated film narratives. To this end, it analyzes the possible functions of colors in animated films, based on the understanding of color theory and its relationship with diegetic reality, especially in the animation Guida (2014), by Brazilian animator Rosana Urbes. Based on a bibliographic review of color theory and its possible insertion in cinema, and supported by a qualitative approach to films analysis, it was possible to map some of the functions of colors in sixteen national and international animations in order to establish a more detailed analysis of the use of colors in the animated short Guida (2014). As a result, it was possible to observe, among other aspects, that colors can assume a range of communicative functions, contributing significantly to the development of film narrative in animated productions.